Immune system disturbances in Clouston syndrome. (9th November 2015) - Pietrzak, Aldona; Grywalska, Ewelina; Gerkowicz, Agnieszka; Krasowska, Dorota; Chodorowska, Grażyna; Michalska‐Jakubus, Małgorzata; Roliński, Jacek; Wawrzycki, Bartłomiej; Radej, Sebastian; Dybiec, Ewa; Wroński, Jacek; Sobczyńska‐Tomaszewska, Agnieszka; et al.
Abstract: Background: Clouston syndrome belongs to the family of ectodermal dysplasias. So far, a defective immune response has not been reported in Clouston syndrome. We report, for the first time, immunological particularities of a large multigenerational Polish family with Clouston syndrome. Methods: Five members of the same family with Clouston syndrome, aged 6–76 years, and 20 healthy volunteers, aged 19–73 years, were enrolled in the study. In all participants, the ability of neutrophils to phagocytize opsonized Escherichia coli was assessed. Granulocyte oxidative burst was determined quantitatively, and an isolation of peripheral blood mononuclear cells and the detection of lymphocyte subsets were performed. All patients with Clouston syndrome underwent microscopic assessment of hair shafts, x‐rays of the skull and hand bones, extra‐ and intraoral examination, and panoramic x‐rays. Results: Compared to the controls, all patients with Clouston syndrome presented with significantly reduced phagocytic activities of granulocytes and monocytes ( P < 0.05). The percentages of granulocytes and monocytes being positive for oxidative burst were also significantly reduced in all patients with Clouston syndrome ( P < 0.05). No disturbances in the percentages and absolute counts of T CD3+, T CD3+/CD4+, T CD3+/CD8+, natural killer, and B CD19+ cells were found. Conclusion: Although this study expands knowledge about Clouston syndrome, it also raises many questions. The results provide evidence of significantly reduced phagocytic activity and oxidative bursts of cells playing crucial roles in a nonspecific immune response. Further studies are required to understand the underlying mechanism of the hereby described abnormalities.